Modelling Moisture Conditions Of Norway Spruce (Picea Abies) : First Validation Against A Global Experiment - Niklewski, Jonas; Emmerich, Lucas; Sand Austigard, Mari; Batista, Djeison; Boivin, Gabrielle; Cai, Lili; Creemers, Jos; Humar, Miha; Hundhausen, Ulrich; Ibáñes, Marcela; Kartal, Nami; Meincken, Martina; et al. (3rd International Conference on Moisture in Buildings 2025, Guimarães, Portugal, 2025-10-23 - 2025-10-24, 2025)
Wood used in outdoor construction is consistently subjected to wetting by precipitation. High levels of moisture content, especially if sustained over long periods, promote fungal decay and structural degradation. Predicting temporal variation of moisture content in wood exposed to rain is essential for durability assessment, and simple fit-for-purpose numerical approaches have been developed for this purpose. While these models do not fully describe the complex dynamics of free water transport, they have been shown to capture the relevant features for durability assessment. Extensive validation is however necessary to assess their applicability, robustness and limitations. This study evaluates a numerical model for moisture content prediction of Norway spruce (Picea abies) boards by comparing its outputs to measurements from 12 locations around the world, all using the same parameter settings. Overall, the model aligned with observed trends and demonstrated robustness across diverse climates, though some discrepancies likely stemmed from weather data inconsistencies and inherent simplifications. The results confirm its reliability for durability-related moisture assessments and suggest refinements to further enhance performance.
This is the author-accepted manuscript of a paper presented at the ICMB25 conference. It was not included in the official conference proceedings due to funder open-access requirements. This version may differ from any subsequently published version.